POSSIBILITY OF CONDUCTING IJMA’I CONSENSUS IN MODERN TIMES - Mawardi, Muhammad Mawardi DJ. (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2023)
Classical Muslim jurists unanimously had provided rulings for many pre-modern religious and mundane issues of Muslims in the past. However, many other classical issues have not been soved this way. Rather, different opinions of different schools of law regarding them have been continuing until today. On the other hand, different type of new human problems and issues have been emerging everyday from the onset of modern time. Since Islam is considered to be a complete and continuing code of life, it should be able to provide solutions and rulings for these new issues. Likewise, in order to maintain harmony and unity of the society, there should be some continuous ways to reduce differences among Muslim jurists. Among others, ijma’ic consensus is deemed to be a source of law and way to remove such disagreements and to deduct new rulings for the issues mentioned above. The purpose of this paper is to investigate whether ijma’i consensus is possible to be conducted at present, in order to reach this objective, the researcher would critically discuss the arguments of both opponents and supporters of this possibility using classical and modern sources. This paper would be divided into five sections: definition of ijma’, arguments of the opponents of conducting ijma’ at present, arguments of the supporters of this idea, critical analysis of the arguments of both groups and preferring one opinion over the other, suggestions for how to conduct an ijma ’i consensus and implement its ruling at present.